Coal mine energy consumption intelligent monitoring system based on cloud platform - YAN DONG; ZHANG XINGCAI; CHEN PENG (2018)
The present invention discloses a coal mine energy consumption intelligent monitoring system based on a cloud platform. The system comprises a cloud platform server and a plurality of energy consumption monitoring terminals dispersed in a coal mine area; each energy consumption monitoring terminal comprises one power module, one central processing unit, one electric energy metering device, one device self-inspection module, one communication module, one alarm module and one Bluetooth location module; the electric energy metering devices, the device self-inspection modules, the communication modules, the alarm modules and the Bluetooth location modules are connected with the central processing units; the cloud platform server is in communication connection with the energy consumption monitoring terminals; and the cloud platform server comprises a data receiving module, a data storage module and a data analysis module which are connected in order; and the power module is configured to supply electric energy. Th